SCHOOL HEADS' SUPPORT AND TEACHING ENGAGEMENT AMONG NEWLY HIRED ELEMENTARY SCHOOL TEACHERS - Jirah Joy T. Iwal; Jesica B. Arenga (CV. ADIBA AISHA AMIRA, 2024)
This study aimed to find out the level of support of the school heads in terms of emotional, professional, instrumental, and appraisal support; the level of teacher engagement in terms of cognitive, emotional, social engagement with students and social engagement with colleagues among the teachers. The significant relationship and influence of these variables are also investigated. Descriptive- correlation research was utilized as research design. The study used validated survey questionnaires that were filled out by the school heads and teachers as respondents who were randomly selected from different schools in the Municipality of Magpet. Results of the study revealed that school heads are very supportive in terms of providing emotional support; professional support, instrumental support and appraisal support to teachers. The newly hired teachers are also highly engaged in terms of cognitive engagement, emotional engagement, social engagement with the students and colleagues. The relationship of the school heads’ support and the teachers’ teaching engagement show a strong correlation with the cognitive; emotional; social engagement with the students; and social engagement with the colleagues. The test of significant influence showed that school heads’ support has significant influence on cognitive; emotional; social engagement with the students; and social engagement with the colleagues. In particular, professional support and appraisal support are best predictors of cognitive engagement of teachers; and only appraisal support significantly predicts emotional engagement; and teachers’ social engagement with the students; and professional support are considered as the best predictors of social engagement with the colleagues.